Action of dichlorobenzimidazole riboside on RNA synthesis in L-929 and HeLa cells (The Rockefeller University Press, 1976)
5,6-Dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) inhibits RNA synthesis in L-929 cells (mouse fibroblast line) and HeLa cells (human epitheloid carcinoma line) within 2 min of addition of the compound to the medium. By removing DRB from the medium, the inhibition is promptly and completely reversed after treatment of cells for as long as 1 h or even longer. The inhibitory effect of DRB on the overall rate of RNA synthesis is similar in L and HeLa cells and is markedly concentration- dependent in the low dose range (5-20 muM or 1.6-6.4 mug/ml), but not as higher concentrations of DRB. At a concentration of 12 muM, DRB has a highly selective inhibitory effect on the synthesis of nuclear heterogenous RNA in L cells. At higher concentrations, there is also inhibition of 45 S ribosomal precursor RNA synthesis, but at all concentrations the effect on heterogeneous RNA synthesis in L cells in considerably greater than that on preribosomal RNA synthesis. In HeLa cells, too, DRB has a selective effect on heterogeneous RNA synthesis, but quantitatively the selectivity of action is somewhat less pronounced. In both L and HeLa cells, the inhibition of synthesis of nuclear heterogeneous RNA is incomplete even at very high concentrations of DRB (150 muM). Thus, while DRB is a selective inhibitor of nuclear heterogeneous RNA synthesis, not all such RNA synthesis is sensitive to inhibition. It is proposed that messenger precursor RNA synthesis may largely be sensitive to inhibition by DRB. In short-term experiments, DRB has no effect on protein synthesis in L or HeLa cells. DRB has a slight to moderate inhibitory effect on uridine uptake into L cells and a moderate to marked effect on uptake of uridine into HeLa cells.